Development of Climate Change Effects-Reducing Information Systems towards Sustaining Medicinal and Aromatic Plants - Oni, Omogbadegun, Zacchaeus (Covenant Journal of Physical and Life Sciences, 2015)
Economic growth has been inextricably linked with accelerating negative environmental impact. Projections show that the full climate change mitigation potential of biotechnology processes and biobased products ranges from between 1 billion and 2.5 billion tons CO2 equivalent yearly by 2030. MAPs‟ species are being destroyed at an unprecedented rate and are threatened with extinction by habitat loss, climate change, overexploitation, land conversion, and deforestation. Global projections of MAPs diversity loss show that the largest losses of habitat and diversity will occur in tropical ecosystems (forest, woodland, savannah), accounting for a projected loss of 25,000 to 40,000 MAPs species by 2050. This paper presents the development of a framework for MAPs productivity and sustainability management. It establishes systems to closely monitor the change in MAPs resources and the recovery of habitats from the unprecedented effects of climate change. A logistic growth model was developed. A conservation program based on MAPs‟ intrinsic rate of increase and carrying capacity parameters was written in C++ programming language. The emerged system ran with varied data to ascertain population growth/harvesting and life span based on flexibility; scalability and modularity; and accuracy would reduce climate effects on MAPs; a framework that presents all the stakeholders and their respective responsibilities in the management of MAPs. The rapid loss of MAPs life has far-reaching consequences, and their loss will adversely affect future drug discovery. The increasing interest of people in MAPs commands a special attention to organize the actors and preserve the MAPs genetic resources against climate change. It is pertinent to improve access to technologies for use in a wider range of MAPs, fostering public dialogue and increasing support for the adoption and use of internationally accepted standards for life cycle analysis together with a range of other incentives designed to reward environmentally sustainable technologies. Key words: Biotechnology, Climate change, Informatics, Conservation, Medicinal and Aromatic Plants, Sustainability